IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMP NEGERI - Harim, Tipan; Ngiu, Zulaecha; Ngilu, Ariyanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aimed to analyze the implementation and inhibiting factors of the Pancasila Student Profile Strengthening Project (P5) implementation at SMP Negeri 6 Satap Telaga Biru. The P5 project is part of the Independent Curriculum, which is designed to shape students' character based on six dimensions: faith and fear of God, global diversity, cooperation, independence, critical reasoning, and creativity. Data in this descriptive qualitative research were collected through observation, interviews, and documentation. Based on the analysis, the P5 has been implemented for three years through the